Neuro axitis - epidemic - Dávila, Mauricio (1929)
I am pleased to submit for consideration by the Faculty, my modest paper entitled: "NEURO - AXITIS EPIDEMIC AND ESPECIALLY PARKINSONISM BRAIN" as an exponent of my efforts. Represents only a sincere effort to contribute something to the best knowledge of the Epidemic encephalitis among us.